Design and Construction of a Website-Based Garment Production Information System - Maulidina, Vidya Ayu Eka; Kukuh, Anang (LPPM STIKI Malang, 2024)
Garment is a specialist production in producing various types of clothing such as ready-to-wear clothing, sportswear, clothing accessories, etc. by utilizing information technology. As time goes by, there are now more and more companies operating in the garment sector and as technology advances, garment companies are now starting to intensively use a system in their production flow. The Garment Industry is a company that operates in the garment manufacturing sector. However, in its operation there are still many problems such as slow operation, less effective data management, manual reporting, missing range data and many more. Administrative activities in garments such as processing order data, order allocation and preparing reports still do not meet operational achievements. Because of this, an information system is needed which is expected to help garment companies solve the problems they face. The role of this information system is the right solution to deal with the problems faced by the company so that everything runs effectively and efficiently. The method that the author used in writing this final assignment was by observing the company premises, conducting interviews with people related to the company, and studying literature from several journals and guidelines for writing this final assignment. Thus, this system is expected to increase the productivity and service quality of garment companies, as well as make a positive contribution to their business growth. The system proposed by the author is web-based, built with a sequence of steps, namely problem identification, needs analysis, coding, design and testing.